2016
DOI: 10.3945/ajcn.115.124636
|View full text |Cite
|
Sign up to set email alerts
|

Including whey protein and whey permeate in ready-to-use supplementary food improves recovery rates in children with moderate acute malnutrition: a randomized, double-blind clinical trial

Abstract: Background: The utility of dairy ingredients in the supplementary foods used in the treatment of childhood moderate acute malnutrition (MAM) remains unsettled. Objective: We evaluated the effectiveness of a peanut-based readyto-use supplementary food (RUSF) with soy protein compared with a novel RUSF containing dairy ingredients in the form of whey permeate and whey protein concentrate in the treatment of children with MAM. Design: We conducted a randomized, double-blind clinical effectiveness trial involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 38 publications
5
69
3
2
Order By: Relevance
“…Recent studies have reported the beneficial effects of whey protein on the health of children, adults and elderly. The growing interest in whey has been noted (Stobaugh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the beneficial effects of whey protein on the health of children, adults and elderly. The growing interest in whey has been noted (Stobaugh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported on morbidity in children with moderate wasting or moderate acute malnutrition (MAM) [9][10][11][12][13][14][15] and most based only on symptom-recall. Current case definitions of MAM includes children with moderate wasting and/or a mid-upper arm circumference (MUAC) between 115 and 125 mm [16].…”
Section: Introductionmentioning
confidence: 99%
“…Ready-to-use supplementary foods (RUSF), with a higher energy density and adjusted micronutrient compositions, were developed for moderately wasted children, as well as pregnant and lactating women (124,(175)(176)(177) . The inclusion of milk protein in RUSF appears beneficial in children recovering from MAM (155) . Two recent intervention studies in Guinea-Bissau demonstrated that RUSF with a higher dairy protein content (33 %) were superior to RUSF with a lower content (15 %) in the community-based management of undernourished preschool children and mothers (154,178) .…”
Section: Growing Commercialisation Of Ready-to-use Foodsmentioning
confidence: 99%